The Relationship Between Lifestyle and the Incidence of Hypertension Complications in the Elderly - Daniel Biru; Roihatul Zahroh; Natalia Christin Tiara Revita (Health Gate, 2026)
Background: Hypertension is a common health problem in the elderly. Symptoms of hypertension are only discovered after complications affect all organs of the body, known as multi-organ dysfunction, including the heart, kidneys, brain, and eyes. Lifestyle plays a significant role in the health of the elderly. An unhealthy lifestyle can increase the risk of hypertension in the elderly. Objective: The purpose of this study was to determine the relationship between lifestyle and the incidence of hypertension complications in the elderly at the Kebomas Gresik Community Health Center. Methods: This study used a cross-sectional design. The population was all elderly at the Kebomas Gresik Community Health Center, with a sample size of 75 respondents. Sampling was conducted using purposive random sampling. The research instrument was a questionnaire. Data analysis used univariate and bivariate analyses. Results: There is a relationship between lifestyle and the incidence of hypertension complications, with a strength of 0.660 within the range of 0.60–0.79. There is a strong relationship between the variables studied. Conclusion: Health education for people with hypertension is needed.